Morin hydrate protects against cisplatin-induced testicular toxicity by modulating ferroptosis and steroidogenesis genes’ expression and upregulating Nrf2/Heme oxygenase-1 - Yasmin Mahran; Amira M. Badr; Sheka Aloyouni; Manal Mubarak Alkahtani; Wedad S. Sarawi; Rehab Ali; Deema Alsultan; Sarah Almufadhili; Dalia H. Almasud; Iman H. Hasan (Scientific Reports)
Abstract Cisplatin is a widely used, effective chemotherapy drug. However, its application is often limited by severe side effects, including testicular toxicity. Cisplatin-induced testicular damage is primarily driven by oxidative stress and inflammation. Ferroptosis has recently been identified to contribute to cisplatin-testicular toxicity. Morin hydrate (MH) is a naturally occurring flavonoid known for its powerful antioxidant, anti-inflammatory, and anti-apoptotic properties. The study was designed to evaluate the protective effects of MH against cisplatin-induced testicular toxicity in Wistar albino rats. Rats were given MH 50 mg/kg, p.o. daily for fourteen days, seven days before the injection of cisplatin 8 mg/kg. Assessment of sperm quality, testosterone, luteinizing hormone levels, and oxidative stress markers were carried out. Also, steroidogenesis and ferroptosis-related gene expressions were assessed. Results: Our findings demonstrated that MH significantly corrected the antioxidant/oxidant balance, evidenced by increased superoxide dismutase, glutathione peroxidase, and Nrf2/heme oxygenase-1 (HO-1) expression and reduced malondialdehyde in testicular tissue. Also, MH ameliorated the negative changes in sperm quality, hormone levels, and testicular histology induced by cisplatin, and this was accompanied by upregulation of steroidogenesis gene expressions (17β-HSD, 3β-HSD, and star). Moreover, MH inhibited cisplatin-induced ferroptosis via the modulation of ferroptosis genes’ expression (ACSL4, SLC7A11, and TFRC) and the reduction of iron accumulation in testicular tissue. Conclusion: MH effectively protected against cisplatin-induced testicular toxicity by reducing oxidative stress and inhibiting ferroptosis signalling. This study points out that MH might mitigate iron-mediated apoptosis through the downregulation of Nrf2/HO-1 signaling, providing a potential therapeutic strategy for preventing infertility in male patients undergoing cisplatin chemotherapy.